2018
DOI: 10.1080/00221686.2018.1478897
|View full text |Cite
|
Sign up to set email alerts
|

Experimental repetitions and blockage of large stems at ogee crested spillways with piers

Abstract: Large wood is often transported by rivers into reservoirs during heavy rainfall events. When a critical section like a spillway is blocked and discharge capacity reduced, an uncontrolled increase of the reservoir water level may occur. This study aims to statistically analyse the importance of repetitions for the accuracy of experimental campaigns when studying blocking probabilities at ogee crested spillways equipped with piers. Systematic and reliable estimations based on physical models are critical for dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Three to four runs with each LW mixture were then performed to capture the random variation in LW jam formation with the same discharge steps and total mixture volume, thus resulting in 15 to 20 independent runs with varying mixtures for each dam. This is less than the high number of repetitions required to capture behaviour of single logs at reservoir dam spillways (Furlan et al, 2019(Furlan et al, , 2020), but we assume it to be sufficient to capture the random variation in the process of large numbers of logs piling up at the dam. This should be validated in later works.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Three to four runs with each LW mixture were then performed to capture the random variation in LW jam formation with the same discharge steps and total mixture volume, thus resulting in 15 to 20 independent runs with varying mixtures for each dam. This is less than the high number of repetitions required to capture behaviour of single logs at reservoir dam spillways (Furlan et al, 2019(Furlan et al, , 2020), but we assume it to be sufficient to capture the random variation in the process of large numbers of logs piling up at the dam. This should be validated in later works.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The second question, i.e. which conditions drive LW overtopping and releases over a structure, has only been ad-dressed for reservoir dam spillways: Pfister et al (2013a) for PK weirs, as well as Furlan et al (2018Furlan et al ( , 2019Furlan et al ( , 2020, Furlan (2019) and Pfister et al (2020) for ogee crests with piles. These studies concluded that the ratio of flow depth to LW diameter was key to determining whether LW stays in the reservoir or overtops the dam.…”
Section: Introductionmentioning
confidence: 99%
“…In alpine environments, the accumulation and the dynamics of debris on river dams and spillways were investigated by Pfister et al (2013) and Furlan et al (2018), among others. Schmocker and Hager (2013) reported that the accumulation of debris upstream of debris rack generated an obstruction of the flow, leading to an increase in the upstream water level.…”
Section: Introductionmentioning
confidence: 99%
“…However, Large Wood elements (LW, with a trunk diameter > 0.1 cm and a length > 1 m, as defined by Wohl et al [38] transported during floods can aggravate the expected drawbacks and augment the overall risk at which the urban areas are exposed [7,8,28].LW may cause obstructions along the channel network, mostly in correspondence of bridges or weirs, where it accumulates, clogging the openings and causing a backwater rise upstream. Hydraulic structures can collapse as a result of the increased loads, and unexpected overflowing can occur at the jammed river cross-sections.The formation of LW accumulation is thus a key issue in the hydraulic risk assessment and its mechanism, as well its subsequent modelling, is still object of study [1,10,13,15,32,34]. It is highly affected by the interactions between water, sediments and structures, and it is also influenced by the physical features of LW element and river morphology [30].Due to the potential implications of LW during floods, different types of practical measures have been developed and employed [2, 5] to retain LW upstream of the critical sections (e.g.…”
mentioning
confidence: 99%
“…The formation of LW accumulation is thus a key issue in the hydraulic risk assessment and its mechanism, as well its subsequent modelling, is still object of study [1,10,13,15,32,34]. It is highly affected by the interactions between water, sediments and structures, and it is also influenced by the physical features of LW element and river morphology [30].…”
mentioning
confidence: 99%